Highly thermally stable Pd/Zn/Ag ohmic contact to Ga-face p-type GaN - Kim, Dae-Hyun; Lim, Weon Cheol; Park, Jae-Seong; Seong, Tae-Yeon (ELSEVIER SCIENCE SA, 2014)
Pd/Zn/Ag ohmic contacts to Ga-face p-type GaN were investigated as a function of annealing temperature. The Pd/Zn/Ag ohmic contacts exhibited a reflectance of 85% at 450 nm, which is higher than that of Ag-only contacts (57%) after annealing at 500 degrees C. The alleviated agglomeration of the Pd/Zn/Ag ohmic contact due to the formation of ZnO at the surface seems to be responsible for the higher reflectance. The specific contact resistances of Ag-only and Pd/Zn/Ag contacts annealed at 500 degrees C were 2.4 x 10 (4) and 6.1 x 10 (5) Omega cm(2), respectively. GaN-based light-emitting diodes (LEDs) fabricated with the Pd/Zn/Ag contacts exhibited similar to 20% higher output power at 20 mA than the LEDs fabricated with the Ag-only contacts annealed at 500 degrees C. On the basis of X-ray photoemission spectroscopy and SEM results, the improved electrical and thermal properties are described. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: LIGHT-EMITTING-DIODES; ELECTRICAL-PROPERTIES; THIN-FILMS; LIFT-OFF; AG; ALLOY; REFLECTANCE; RESISTANCE; EFFICIENCY; STABILITY